Mimicking natural polymorphism in eIF4E by CRISPR‐Cas9 base editing is associated with resistance to potyviruses - Bastet, Anna; Zafirov, Delyan; Giovinazzo, Nathalie; Guyon‐Debast, Anouchka; Nogué, Fabien; Robaglia, Christophe; Gallois, Jean‐Luc (Plant biotechnology journal, 2019)
Summary In many crop species, natural variation in eIF4E proteins confers resistance to potyviruses. Gene editing offers new opportunities to transfer genetic resistance to crops that seem to lack natural eIF4E alleles. However, because eIF4E are physiologically important proteins, any introduced modification for virus resistance must not bring adverse phenotype effects. In this study, we assessed the role of amino acid substitutions encoded by a Pisum sativum eIF4E virus‐resistance allele (W69L, T80D S81D, S84A, G114R and N176K) by introducing them independently into the Arabidopsis thaliana eIF4E1 gene, a susceptibility factor to the Clover yellow vein virus (ClYVV). Results show that most mutations were sufficient to prevent ClYVV accumulation in plants without affecting plant growth. In addition, two of these engineered resistance alleles can be combined with a loss‐of‐function eIFiso4E to expand the resistance spectrum to other potyviruses. Finally, we use CRISPR‐nCas9‐cytidine deaminase technology to convert the Arabidopsis eIF4E1 susceptibility allele into a resistance allele by introducing the N176K mutation with a single‐point mutation through C‐to‐G base editing to generate resistant plants. This study shows how combining knowledge on pathogen susceptibility factors with precise genome‐editing technologies offers a feasible solution for engineering transgene‐free genetic resistance in plants, even across species barriers.